Mixture effects of azole fungicides on the adrenal gland in a broad dose range. (15th June 2017) - Rieke, S.; Heise, T.; Schmidt, F.; Haider, W.; Bednarz, H.; Niehaus, K.; Mentz, A.; Kalinowski, J.; Hirsch-Ernst, K.I.; Steinberg, P.; Niemann, L.; Marx-Stoelting, P.
Abstract: Consumers are exposed to low concentrations of a variety of pesticide residues in or on food. Some of them might interfere with the endocrine system. While each individual active substance has been extensively tested for toxicity and safety, potential combination effects possibly resulting from combined exposure to different pesticides have seldomly been tested so far, especially in vivo . Since the adrenal gland is a key endocrine organ, we investigated if and how substances of a group of fungicides presumed to interfere with the biosynthesis of steroid hormones affect this organ when applied individually and in combination in a broad dose range. A 28-day feeding study was conducted in Wistar rats by using three (tri)azole fungicides considered to potentially affect the endocrine system (cyproconazole, epoxiconazole and prochloraz) individually at five dose levels, ranging from 0.9 ppm to 2400 ppm, and in combination at three dose levels. The parameters analysed included classical toxicology (pathology, histopathology, clinical chemistry) and molecular toxicology endpoints (gene expression arrays and quantitative real time PCR e.g. of Star, HSD 3β, Cyp11a1, Cyp11b1, Cyp11b2, Cyp 21, ApoE ), as well as hormone analysis. A dose-dependent decrease in the adrenal gland weight of rats treated with epoxiconazole alone, which was accompanied by an atrophy of the adrenal gland as well as by an increase in the serum cholesterol level and which only became statistically significant at the top dose levels, was observed. These effects were attenuated in the combination experiments, although the same epoxiconazole concentration was used.